Salivary immunoglobulin A and upper respiratory symptoms during 5 months of training in elite tetraplegic athletes - Leicht, C. A.; Bishop, N. C.; Paulson, T. A. W.; Griggs, K. E.; Goosey-Tolfrey, V. L. (International Journal of Sports Physiology and Performance, 2012)
Purpose: Altered autonomic innervation in tetraplegic individuals has been shown to depress certain immune parameters at rest and alter exercise-related salivary immunoglobulin A (sIgA) responses. The purpose of this study was to examine resting sIgA responses as a function of training load and episodes of upper respiratory symptoms (URS) in elite tetraplegic athletes. Methods: Resting saliva samples were obtained from 14 tetraplegic athletes at 12 predefined time points over 5 months and analyzed for sIgA. Occurrence of self-reported URS and training load was recorded throughout the study`s duration. Regression analyses were performed to investigate the relationship between sIgA responses and training load. Furthermore, the relationships between sIgA responses and URS occurrence were examined. Results: sIgA secretion rate was negatively correlated with training load (P = .04), which only accounted for 8% of the variance. No significant relationships were found between sIgA responses and subsequent URS occurrence. Finally, sIgA responses did not differ between athletes with and without recorded URS during the study period. Conclusions: In line with findings in ablebodied athletes, negative relationships between sIgA secretion rate and training load were found in tetraplegic athletes. This may explain some of the higher infection risk in wheelchair athletes with a high training load, which has been previously observed in paraplegic athletes. However, the nonsignificant relationship between sIgA responses and URS occurrence brings into question the use of sIgA as a prognostic tool for the early detection of URS episodes in the studied population.